Desert cabal : a new season in the wilderness - Irvine, Amy; Spalding, Blake; Lopez-Whiteskunk, Regina (2018)
On the 50th anniversary of the publication of Edward Abbey's Desert solitaire: a season in the wilderness, author Amy Irvine has produced a clutch of essays in praise of Abbey's work, and also as a correction to some of his dated and offensive attitudes
Keywords: Abbey, Edward, -- 1927-1989.; Desert biology -- West (U.S.); Deserts -- West (U.S.); Desert conservation -- West (U.S.); Wilderness areas -- West (U.S.); Nature conservation -- West (U.S.); Nonfiction